The Effect of Natural and Cultural on Poverty Reduction in Medan North Medan - OK. Henry (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Poverty is one of the main problems of development which is complex and multi-dimensional, where the phenomenon is influenced by various interrelated factors, including natural and cultural. Poverty is no longer understood as merely an economic incapacity, but also a failure to fulfill basic rights and different treatment for a person or group of people in living a life with dignity. The purpose of this research is about natural poverty which from the beginning was poor and cultural poverty is an attitude of life of a person or group caused by lifestyle. This research method is quantitative research with data collection by interviewing and using questionnaires directly and indirectly. The measuring instrument used is the validity and reliability test. From the results of this study, it was found that natural poverty has a negative and significant effect on poverty alleviation while cultural poverty on poverty reduction has a positive and significant effect on poverty alleviation in North Medan, Medan City. In formulating poverty alleviation programs in North Medan, Medan City.